Hubungan kecerdasan emosi dengan perilaku agresi remaja di Bandar Lampung - Triyoso Triyoso (JOURNAL OF Mental Health Concerns, 2022)
Background: Today we often hear and even see acts of violence that occur in our surroundings, both verbally and non-verbally. Not infrequently also in the family, community and school environment. Families that should be role models for their sons and daughters, whether consciously or not, are now turning their backs on harm. One of the factors that influence aggressive behavior is thought to be emotional intelligence. Purpose: To determine the relationship between emotional intelligence and adolescent aggression behavior in Bandar Lampung. Methods: This research uses a non-experimental quantitative method with a comparative causal type, which wants to know the factors that influence the variables of adolescent aggression behavior. The sampling technique was non-probability sampling with purposive sampling, with a sample of 100 youths in Bandar Lampung. The results of the regression test obtained a sig (p) of 0.000 (<0.05) meaning that the hypothesis is accepted, namely that there is a positive influence of emotional intelligence on aggressive behavior in adolescents in Bandar Lampung. Results: characteristics of respondents with an average age of 16.80 and an age range of 14-18 years. From the sex of the majority male with a percentage of 52 percent, have high aggressive behavior 57 percent, poor emotional intelligence 52 percent, do not consume alcohol 87 percent, people who influence the majority of parents with a percentage of 52 percent and cause of stress the majority of learning tasks with a percentage of 63 percent. Conclusion: There is a relationship between emotional intelligence and aggressive behavior with a p-value <0.05.   Pendahuluan: Dewasa ini kita sering kali mendengar bahkan melihat tindak kekerasan yang terjadi dalam lingkungan sekitar kita baik secara verbal maupun non verbal. Tidak jarang pula pada lingkungan keluarga, masyarakat maupun sekolah. Keluarga yang seharusnya menjadi contoh teladan bagi putra putrinya, entah itu secara sadar atau tidak, sekarang justru berbalik mencelakai. Salah satu faktor yang mempengaruhi perilaku agresi diduga adalah kecerdasan emosi. Tujuan: Untuk mengetahui hubungan kecerdasan emosi dengan perilaku agresi remaja di Bandar Lampung. Metode: Penelitian ini menggunakan metode kuantitatif non eksperimental dengan jenis kausal komparatif, yang ingin mengetahui factor-faktor yang berpengaruh terhadap variabel perilaku agresi remaja. Teknik pengambilan sampel non probability sampling dengan jenis purposive sampling, dengan sampel sebanyak 100 remaja di Bandar Lampung. Hasil uji regresi didapatkan sig (p) sebesar 0,000 (< 0,05) artinya hipotesis diterima yaitu terdapat pengaruh positif kecerdasan emosi terhadap perilaku agresi pada remaja di Bandar Lampung. Hasil: karakteristik responden dengan rata-rata usia 16.80 dan rentang usia 14-18 tahun. Dari jenis kelamin mayoritas laki-laki dengan persentase 52 persen, memiliki prilaku agresi tinggi 57 persen, kecerdasan emosi buruk 52 persen, tidak mengkonsumsi alkohol 87 persen, orang yang berpengaruh mayoritas orang tua dengan persentase 52 persen dan penyebab stress mayoritas tugas belajar dengan persentase 63 persen. Simpulan: Terdapat hubungan antara kecerdasan emosi dengan prilaku agresi dengan hasil p-value < 0,05.